Penerapan Nilai dan Adab dalam Manuskrip Melayu-Islam: Suatu Analisis Terhadap MSS 4291(A) Tahdhir Al-Walad: The Implementation of Values and Manners in Malay-Islamic Manuscript: An Analysis of MSS 4291(A) Taḥdhīr al-Walad - Mamat, Mohd Anuar (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
During the era of manuscript writing in the Malay Archipelago from the 16th to the 19th century, various texts were produced by Malay scholars. This is evidenced by the discovery of various Malay manuscripts in all aspects of knowledge. Among the unique features of the works produced, particularly the manuscripts in sastera kitab genre, the writings that are based on values and aim to instil good manners (adab) to the readers. The production of works like this is extensive, not only in prose form but also in other forms, such as poetry, syair (traditional Malay poetry), and nazam (a type of poetic recitation). Therefore, this article will discuss the implementation of values and manners in one of the Malay-Islamic manuscripts from the National Library of Malaysia's collection, MSS 4291(A), entitled Taḥdhīr al-Walad. This manuscript is written in the form of poetry that contains explanations about the core values and manners that should be instilled in students and society. It is written using the Arabic language and accompanied by interlinear translations to facilitate understanding for new students and readers. This article applied manuscript studies methods, including codicological analysis to examine the physical aspects and historical background of the manuscript, as well as philological analysis to transliterate the text from Arabic and Jawi script to Roman script. Content analysis is then used to explore the key values and the application of manners in the poetic text of Taḥdhīr al-Walad. Through the study of the manuscript and textual analysis, the aim is to highlight the values and manners embodied in Malay-Islamic manuscripts, specifically in the form of poetry and syair, and to make these values accessible and applicable to contemporary society.